A Reforma, os santos e a religião do povo na América Latina - Rieth, Ricardo (Revista eclesiástica brasileira, 2000)
Latin American protestantism created its own identity by, among other things, an intense and systematic anti-Catholicism. Everything that has to do with veneration or highlighting the memory of the Saints was, and in many cases still is, condemned as idolatty. This article asks about the co-herence of this position, having in mind the histoiy and the theology of the Lutheran Reformation. It tries to contribute, in this way, to the theological and ecumenical dialogue having to do with a fundamental theme of Latin American spirituality.